The Process of Choosing, Structuring and Refreshing the Content of the Professional Disciplines in the Professional Future Foreign Language Teachers’ Preparation - Dubrova, Svitlana (Pedagogical Discourse, 2014)
In the article we describe the process of choosing, structuring and refreshing the content of the professional disciplines in the professional future foreign language teachers’ preparation. We describe and analyze basic principles which are used in choosing the content of the professional disciplines. These are thematic and situational, simplicity, succession and systematic, problematic, unity of the theory and practice. In the article we defined main components of the educational material: language skills and abilities, language material, sociolinguistic and pragmatic knowledge which is the base of the skills’ formation, language material (educational texts for reading and speaking), topics and situations of communication. Also we made clear that according to its functions educational material belongs to such types: informational, operational, actual, controlling, stimulative, diagnostically. We determine that in the process of structuring educational material teachers choose the minimum and maximum its content for learning, fix the content’s center of each topics, distinguish the main professional concepts and ideas, set up links between them, define the rules for the application of these concepts, choose the appropriate exercises and tasks. Teachers constantly work at improving, adding, processing and adapting of the educational material in accordance with modern requirements and new technologies.